2007
DOI: 10.1590/s0103-84782007000100014
|View full text |Cite
|
Sign up to set email alerts
|

Growth and physiological responses of sunflower plants exposed to ultraviolet-B radiation

Abstract: The effects of UV-B radiation were studied in sunflower plants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
9
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
6
9
0
4
Order By: Relevance
“…In the UV-B stressed almond plants, the decrease in Chl a, Chl b, and Chl (a+b), suggests a possible damage of the light-harvesting complex. Similar responses were observed in Sinapsis alba (Jennifer et al 2000) and Helianthus annuus L. (Cechin et al 2007) plants.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In the UV-B stressed almond plants, the decrease in Chl a, Chl b, and Chl (a+b), suggests a possible damage of the light-harvesting complex. Similar responses were observed in Sinapsis alba (Jennifer et al 2000) and Helianthus annuus L. (Cechin et al 2007) plants.…”
Section: Discussionsupporting
confidence: 74%
“…Several studies have confirmed the deleterious effects of UV-B radiation on photosynthetic processes (Keiller and Holmes 2001, Mészáros et al 2001, Correia et al 2005, Cechin et al 2007) but less is known about the way how UV-B radiation affects photosynthetic activity in almond plants. The significant reduction in P N suggests that UV-B treatment can affect photosynthesis by affecting enzyme activity, primary photochemistry, electron transport, biochemical reactions of the Calvin cycle, as well as changes in the structure of the chloroplasts (Borman 1989, Ambasht and Agrawal 1995, Balakrishnan et al 2005, Cechin at al. 2007.…”
Section: Discussionmentioning
confidence: 99%
“…The content of phenolics was not significantly modified under exposure to supplementary UV radiation either. Our results are consistent with the previously published findings [4,19]. Minor changes in the concentrations of photosynthetic pigments can probably be attributed to the short time of UV-B exposure.…”
Section: Resultssupporting
confidence: 93%
“…La radiación UV-B no afecta la biomasa, materia seca de brotes, peso específico de las hojas ni compuestos absorbentes de UV-B del girasol cultivado en invernadero y esto se debe a la temprana etapa de desarrollo en la que se impuso el estrés (Cechin et al, 2007), ya que la planta puede aumentar el espesor de la hoja como respuesta al estrés por radiación UV-B (Liu et al, 2005) disminuyendo de esta forma el daño UV-B, de lo contrario, al no darse un incremento en el espesor de la hoja la radiación UV-B alcanza el mesófilo y puede afectar el proceso de fotosínte-sis. Por esta razón, la radiación UV-B inhibió significativamente la fotosíntesis acompañada por una reducción en la conductancia estomática y en la transpiración, aunque el contenido total de clorofila y la eficiencia máxima potencial del PS II no se vieron afectados.…”
Section: Estrés Por Radiación Ultravioleta-bunclassified
“…Por esta razón, la radiación UV-B inhibió significativamente la fotosíntesis acompañada por una reducción en la conductancia estomática y en la transpiración, aunque el contenido total de clorofila y la eficiencia máxima potencial del PS II no se vieron afectados. En general, el estudio de Cechin et al (2007) sugiere que a pesar de que la biomasa seca no se afecte, el nivel actual de radiación UV-B solar afecta el rendimiento de las plantas de girasol.…”
Section: Estrés Por Radiación Ultravioleta-bunclassified